Discrete quantum mechanics - Odake, Satoru; Sasaki, Ryu (Journal of physics. A, Mathematical and theoretical, 2011)
A comprehensive review of the discrete quantum mechanics with the pure imaginary shifts and the real shifts is presented in parallel with the corresponding results in the ordinary quantum mechanics. The main subjects to be covered are the factorized Hamiltonians, the general structure of the solution spaces of the Schrodinger equation (Crum's theorem and its modification), the shape invariance, the exact solvability in the Schrodinger picture as well as in the Heisenberg picture, the creation/annihilation operators and the dynamical symmetry algebras, the unified theory of exact and quasi-exact solvability based on the sinusoidal coordinates, and the infinite families of new orthogonal (the exceptional) polynomials. Two newinfinite families of orthogonal polynomials, the X sub(l)Meixner-Pollaczek and the X sub(l)Meixner polynomials, are reported.